2003
DOI: 10.1097/01.tp.0000067529.82245.4e
|View full text |Cite
|
Sign up to set email alerts
|

Role of ischemic preconditioning and the portosystemic shunt in the prevention of liver and lung damage after rat liver transplantation1

Abstract: These findings indicate that ischemic preconditioning could be a preferred treatment to reduce hepatic and pulmonary damage associated with liver transplantation. However, this strategy may not be effective in several clinical situations requiring a portosystemic shunt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 47 publications
0
17
1
2
Order By: Relevance
“…This could prevent the deleterious effects of TNF on the liver and promote liver regeneration following ROLT. Indeed, the reduction in TNF release following hepatic I/R induced by ischemic preconditioning has been previously reported in normothermic and cold ischemia conditions without hepatectomy (28)(29)(30). However, in our hands, ischemic preconditioning did not modify the levels of either IL-6 or TNF in reduced-size liver grafts after transplantation.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…This could prevent the deleterious effects of TNF on the liver and promote liver regeneration following ROLT. Indeed, the reduction in TNF release following hepatic I/R induced by ischemic preconditioning has been previously reported in normothermic and cold ischemia conditions without hepatectomy (28)(29)(30). However, in our hands, ischemic preconditioning did not modify the levels of either IL-6 or TNF in reduced-size liver grafts after transplantation.…”
Section: Discussioncontrasting
confidence: 45%
“…The use of ischemic preconditioning in reduced-size liver transplantation should be considered, as Clavien et al reported the first clinical application of ischemic preconditioning during normothermic ischemia associated with hepatic resections (26). In addition, results of experimental hepatic ischemia without liver resection suggest that ischemic preconditioning could modulate the negative effects of I/R on hepatic regeneration (24,(27)(28)(29)(30). Thus, ischemic preconditioning protects Table 1: Flow chart of the interventions and measurements corresponding to protocols 1, 2, 3 and 4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…İskemik önkoşullamanın olumlu etkilerinin gözlendi-ği diğer en önemli organ karaciğerdir. Yapılan çalış-malarda, ısı şok ile oluşturulan önkoşullama sayesinde iskemiye karşı hepatik korunma sağlanmıştır (24) . Ortotopik karaciğer transplantasyonlarında hepatik önkoşullamanın büyük önem taşıdığı bir gerçektir (24) .…”
Section: Mi̇yokard Dişi Doku Ve Organlarda İskemi̇k öNkoşullamaunclassified
“…Tsuyama et al [133] reported that IPC prolonged survival, suppressed liver necrosis induced by IRI and inhibited the release of TNF-α at 1 h, and IL-6 at 2 and 5 h of the reperfusion phase in mice. IPC has also been shown to reduce TNF-α production in normothermic and cold ischaemic conditions [125,134,135] . In contrast, Bedirli and others demonstrated that IPC inhibited the production of TNF-α, but not IL-6 during the late (24 and 48 h) phases of reperfusion in rats following partial hepatectomy [136] .…”
Section: Up-regulation Of the Regenerative Cytokine Network Tumour Nementioning
confidence: 99%